(untitled) (Balthazar, 2023)
Using water, mirroring and the concept of surface as a compass, the essay aims to highlight the points of contact between the words and works of Iosif Brodskij, J.M.W. Turner, John Ruskin and Venice, the city that embraced their gaze.